Harnessing the Power of Artificial Intelligence(AI) for Predicting Nutritional At-Risk Children - Somen Saha; Deepak B Saxena (Healthline, 2023)
Artificial intelligence (AI) is a new buzz word for various public health solutions, AI is expected to transform India’s dream of affordable universal healthcare into reality. India has been rapidly transformed the power of AI in diagnostic services, addressing shortage of human resource, and hospital management services. However, there is a huge potential to transform the power of machine learning for examining the huge data and records collected under mother and child tracking systems for health and nutrition at risk assessment.